2016
DOI: 10.7317/pk.2016.40.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crosslink Agents on Sodium Alginate and Lignosulphonic Acid Blends

Abstract: Blends of sodium alginate (SA) and lignosulphonic acid (LS) has been prepared in the ratio of 80/20. The prepared blends were crosslinked using chlorides of calcium, barium, strontium and aluminum. The crosslinking of blends was done for different time intervals and then these blends were subjected for swelling studies in aqueous medium of pH 7.4. The observations indicate that the crosslinking is diffusion controlled and is affected by the size of metal ion and the type of alginate used. The improved swelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The swelling behavior of hydrogels depends on hydrogen bonding between hydrogel polymer chains and water molecules, and can be strongly affected by cross-linker chemistry. 27 Thus, increased cross-linker reaction…”
Section: Resultsmentioning
confidence: 99%
“…The swelling behavior of hydrogels depends on hydrogen bonding between hydrogel polymer chains and water molecules, and can be strongly affected by cross-linker chemistry. 27 Thus, increased cross-linker reaction…”
Section: Resultsmentioning
confidence: 99%
“…The lower swelling capacity can also be attributed to the difference in complexation of NaAlg with various cations. It can be noted that NaAlg forms stronger crosslinked hydrogels with CaCl 2 compared to Al 2 (SO 4 ) 3 [9]. Similarly, in another study, the amount of time the polymer solution was left to crosslink also affected the water uptake or the hydrogel's swelling capacity [10].…”
Section: Characteristics Of Hydrogel Swellingmentioning
confidence: 99%
“…It is also reported that the strength of alginate film with Al 3+ ion is very low compared to other divalent ions (Ca 2+ and Ba 2+ ) crosslinking because in the case of Al 3+ ions the crosslinking occurs in two different planes of the alginate structure and at the same time it makes the alginate framework more compact [31]. The small size of the Al 3+ ion (0.58 A) facilitates its diffusion into the matrix of the film without crosslinking on the surface and thus results in poor crosslinking [32].…”
Section: Gelling Propertiesmentioning
confidence: 99%